Unveiling Risk Profiles: A Latent Profile Analysis of 21st‐Century Skills, Resistance to Change, and Cognitive Flexibility - Muhammed Celal Uras; Suat Kaya; Alican Kaya; Murat Yildirim (Brain and Behavior)
ABSTRACT Objectives Limited research utilized a person‐centered approach in examining 21st‐century skills. This study used latent profile analysis to explore the relationships between resistance to change, cognitive flexibility, and 21st‐century skills, including creativity, cooperativity, critical thinking, communication, and problem‐solving. Materials and Methods A convenience sampling approach was used to recruit 502 individuals (342 females; meanage = 21.12 ± 2.34 years) via an online survey. Results The results showed that creativity, cooperativity, critical thinking, communication, problem‐solving, and resistance to change were determined as profile indicators. The cognitive flexibility of the subclasses was also predicted. Furthermore, the results revealed four distinct profiles: (i) average level across all skills (5.8%); (ii) low risk for most skills, moderate for cooperativity (18.1%); (iii) high risk for all skills (55.2%); and (iv) moderate risk for most skills, moderate for cooperativity (20.9%). Conclusions The study highlights the importance of cognitive flexibility in identifying risk profiles. Using mixture modeling provides a fresh perspective for researchers, potentially aiding in targeted interventions for at‐risk university students to enhance their 21st‐century skills.